Strategi Perencanaan Keuangan Era Pandemi Covid 19 Pada Umkm Kain Ulos Di Desa Pahlawan Kabupaten Batu Bara - Irawan Irawan; Marahadi Siregar (University of Muhammadiyah Sumatera Utara, 2020)
The goal to be achieved from this service is to increase the understanding and knowledge of SME entrepreneurs, Kain Songket, in carrying out financial planning for the Covid-19 Pandemic era. Then it is also hoped that Kain Songket's UMKM business actors will be able to optimize business opportunities properly so that the needs of Kain Songket and UMKM businesses are met and achieving the survival of the efforts of the Covid 19 pandemic era. Desa Pahlawan, located in Batu Bara Regency, is a village located in a coastal area with 70% of the people working as laborers and fishermen, the rest are business actors. The low level of welfare is mainly due to low income and poor consumption patterns. This service plan will be carried out for 30 days starting from field observations to counseling with the theme of improving understanding of financial planning properly. It is known that to carry out financial planning, Kain Songket's UMKM business actors have been equipped with an understanding including defining financial goals specifically, can be measured (measurable), can be achieved (realistic) or reasonable, not imaginations that cannot be realized. and has a target timeframe (time-frame). Creating a program for evaluating business development by developing an action plan for financial planning during the Covid-19 pandemic. Making implementation in the form of planning short-term and long-term needs, establishing priority financial goals, and utilizing stimulus financial assistance from the Government in the face of the Covid-19 pandemic